If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45z + -90z = 0 Combine like terms: 45z + -90z = -45z -45z = 0 Solving -45z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '-45'. z = 0 Simplifying z = 0
| 6x[5x-7]=432 | | x+1=44 | | 13-9x=51-2x | | 7a+9b= | | 3(a-2)+5w=22 | | 2x^3+5x^2-12=0 | | -19-9x=10x+23 | | 3m+4-9m=-9-6m+23 | | 16x-8=14x+4 | | 3(3+6x)-3=114 | | 6-68= | | 68-6= | | 5x+2(6x-8)=120 | | 17.92=x-0.2x | | 35e+23-30e=48 | | 4(3x-3)=24 | | 13-6x=3x+24 | | 5z-6=x | | 1+2x=9+3x | | -w^2-3w-7=-2w^2+3 | | 37-3x+10x=2 | | 2(3x-5)=7(x-2) | | 48x^2-84x+36=0 | | 6xd=24 | | 4a-(a+6)=12 | | 11-5x=-7x-15 | | 4a+1+-a=19 | | 12-x-5x=-198 | | 6x-2=10x-10 | | 7p-5-6p=8 | | 2x+3=3(x+8) | | y+2-x= |